Lusitanian Personal Names with the Equine Motivation - Witczak, Krzysztof (Lingua Posnaniensis, 2010)
The aim of this article is to find an equine motivation for several personal names attested in the territory of the Roman Lusitania. New or better Indo-European reconstructions (e.g. *melyos and *ku-melyos ‘horse; stallion’; IE. *k∂nkilos and *k∂nkanos ‘horse’, as well as the root *k∂nk-) in reference to the animal terminology are suggested. The distribution of the reflexes of IE. *ekwos ‘horse’ and *k∂nkilos / *k∂nkanos ‘id.’ in the area of the Hispanic Peninsula is carefully explained. Finally it is concluded that the horse and bull were the most esteemed animals in the culture of the ancient Lusitanians.